1996
DOI: 10.1021/js9504752
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA is Protected against Ultrasonic Cavitation-Induced Damage when Complexed to Cationic Liposomes

Abstract: Cationic liposomes bound to plasmid DNA are currently used for in vitro and in vivo gene therapy applications, but such complexes readily form large, heterogeneous aggregates that are not appropriate for pharmaceutical development. More importantly, size heterogeneity makes studies focused on optimizing gene transfer to cells difficult to conduct or understand. For this reason we have evaluated the effect of microprobe sonication on these complexes in an effort to achieve process-controlled size homogeneity. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 52 publications
2
36
0
1
Order By: Relevance
“…These data also suggest that sonication did not damage the DNA, which can occur at conditions more extreme than those used in this study [40]. Although not observed here, previous work has shown that complexing DNA with cationic polymers and lipids can increase the stability of plasmid DNA during sonication [18,40,45,46].…”
Section: Discussionsupporting
confidence: 69%
“…These data also suggest that sonication did not damage the DNA, which can occur at conditions more extreme than those used in this study [40]. Although not observed here, previous work has shown that complexing DNA with cationic polymers and lipids can increase the stability of plasmid DNA during sonication [18,40,45,46].…”
Section: Discussionsupporting
confidence: 69%
“…This may, in turn, be an important factor in designing effective lipid-based DNA delivery systems (3). However, the degree to which aggregation occurs following addition of DNA to cationic liposomes varies with different liposomal lipid composition (6), and the lipid structures generated as a consequence of the aggregation events are also dependent on the cationic liposomes used. Differences in lipid composition did not, however, appear to influence the level of DNA delivery in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident, however, that the liposome-DNA aggregates are heterogeneous with respect to size and shape (5,6) and generate highly complex fused structures as shown by electron microscopy (7,8). Transfection can be achieved using this heterogeneous population of aggregates, but the complex that is directly responsible for mediating the transfection process is still unknown.…”
mentioning
confidence: 99%
“…At high positive or negative charge ratios, relatively small complexes are formed, whereas large aggregates are usually formed when the net charge is close to neutrality (Eastman et al, 1997;Almofti et al, 2003). The cationic liposomes used are typically small (ϳ100 nm) before adding to DNA; however, complexes formed with DNA exhibit diameters that range from as small as 200 nm to structures as large as 2 m (Wasan et al, 1996). The formation of lipoplexes is generally difficult to control, and different structures are produced in the same lipoplex preparation.…”
Section: A Interaction Between Dna and Cationic Lipids Or Polymersmentioning
confidence: 99%